Occupational choices of school-going adolescents: a study in the Pitseng Area, Leribe District, Lesotho - Mookho Makhata; Deshini Naidoo; Thavanesi Gurayah (James Cook University, 2021)
Introduction: Adolescents require opportunities to engage in occupations and need to have the requisite aptitude and agency to choose the occupations they want or need to engage in. Occupations are defined as the everyday activities that people choose to engage in individually or as groups that bring meaning and purpose to their lives. These occupations can be chosen or enforced. There is a paucity of literature around the occupations that adolescents in rural contexts choose and the meaning underlying their choices. This study explored the occupations of school-going adolescents of Pitseng, Lesotho, to gain insight into adolescent behaviour, and the strategies needed to develop sustainable health promotion programs for adolescents in this area. Methods: A descriptive qualitative research design was used. Purposive sampling was used to recruit 47 adolescents aged between 13 and 15 years from three high schools in Pitseng, Leribe district, Lesotho. Data was collected using focus group interviews after consent was obtained from the parents or caregivers and assent from the adolescents. Data were analysed thematically using Braun and Clarke's method. Results: Three main themes emerged from the study: realities of customary rural life, facilitators of occupational engagement, and wellbeing versus risky behaviour. Participation in daily routine occupations, cultural norming, resource scarcity, school milieu and leisure engagement were subthemes derived under the first theme. The subthemes identified under the theme facilitators of occupational engagement were intrinsic motivation, and vicarious modelling and peer support. The third theme encompassed the conceptualisation of wellbeing and risky behaviour as subthemes. The adolescents were found to engage in risky behaviour to escape the monotony in their daily lives. This could be attributed to them having fewer choices for recreational activities during their free time. Some adolescents were able to improvise and attempted to enjoy their lives with fewer occupational choices. The natural environment, coupled with creativity, facilitated the engagement of adolescents in fun activities. Conclusion: The dominant influences relating to the adolescents' occupational choices and participation in activities were the impoverished rural context and the traditional inherited practices. The protracted timeframes for completing basic activities and household responsibilities and the scarcity of resources for leisure led to a restricted range of leisure activities. The traditional cultural context influenced gender-based differences in the manifestation of occupations. Despite the challenges, the adolescents showed resilience, creativity and a strong desire to improve their futures. Moreover, in this culturally steeped environment, the school and the community chief may be the two best entry points for organisations planning to facilitate health promotion programs. They are recognised and sanctioned power bases in rural communities. Recommendations for education, leisure, health promotion and further study were made for Pitseng.